Pemeriksaan Radiologi sebagai Upaya Skrining dan Deteksi Dini Kanker Paru - Sulistyowati, Indah; Rosidah, Siti (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Lung cancer is one of the most common cancers suffered by people in the world, especially those who have a habit of smoking. But unfortunately, many of those who suffer from lung cancer get help too late because they are late or do not realize the symptoms that appear. Because it is too late, the success of the treatment is also low because they ignore the symptoms that appear from the start. The goal to be achieved in this community service activity is to increase knowledge about lung cancer and a healthy lifestyle with CERDIK behavior and increase public awareness and concern to carry out screening and early detection of lung cancer for people at risk. After the community service program was implemented with lecture, discussion and question and answer methods. The results obtained were an increase in knowledge about lung cancer, a healthy lifestyle with CERDIK behavior in partner group members. As well as an increase in the ability and awareness of partner group members in implementing a healthy lifestyle with CERDIK behavior and efforts to screen and detect lung cancer early with radiological examinations.